The eleventh scientific Olympiad of Iranian medical students: Challenges and solutions - Mohammad Esmaiel Hajinezhad; Alireza Yousefi; Fariba Jowkar (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The scientific Olympiad is an event that creates a competitive environment for student groups of medical universities across the country to solve problems that can help improve the health system. This study aims to explain the issues of the scientific Olympiad program of Iranian medical students. MATERIALS AND METHODS: This study was conducted using content analysis method, and the data were collected through 21 semi-structured, in-depth interviews with experts from December 2018 to April 2020. Participants were selected using purposive sampling methods. Twenty-one students, domain leaders, question designers, Olympiad executive experts, and teachers (11 males and 10 females) participated in the interviews. Data analysis was performed based on the steps of Graneheim and Lundman's method. The interviews were recorded, transcribed, and subjected to a qualitative analysis by MAXQDA 2018 software. RESULTS: From the analysis of data, four themes, including inattention to context, inattention to input, inattention to process, and inattention to output, emerged. CONCLUSIONS: The scientific Olympiad can lead to interuniversity scientific exchanges and paves the way for the promotion of education and evaluation of learners in medical universities, but if not correctly implemented and the problems of previous periods are not solved, it will not help the health system and can impose considerable costs on the system.